Psychological and gender specific correlates of aggressive behaviour in military personnel - Ya. S. Ponomarenko; N. V. Hresa; V. M. Filonenko (Bulletin of Kharkiv National University of Internal Affairs)
Participation in conflicts can have a significant impact on the manifestation of aggression among military personnel, especially those who have had intensive combat experience in war zones. The key aspects of gender psychology and the influence of military factors on aggressive behaviour are considered. The term “gender-based aggression” in military personnel is proposed, which reflects the concept that describes the difference in the manifestations of aggressive behaviour depending on the gender characteristics of a person. It is used to analyse and understand how gender and psychological factors influence the perception and expression of aggression among men and women, particularly in the context of military settings. The purpose of the study is to identify and analyse the psychological and gender factors associated with aggressive behaviour of military personnel.